Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1038/nm0798-814
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of stimulated homologous macrophages results in partial recovery of paraplegic rats

Abstract: Postinjury recovery in most tissues requires an effective dialog with macrophages; however, in the mammalian central nervous system, this dialog may be restricted (possibly due to its immune-privileged status), which probably contributes to its regeneration failure. We circumvented this by implanting macrophages, pre-exposed ex vivo to peripheral nerve segments, into transected rat spinal cord. This stimulated tissue repair and partial recovery of motor function, manifested behaviorally by movement of hind lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
412
1
9

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 733 publications
(433 citation statements)
references
References 50 publications
11
412
1
9
Order By: Relevance
“…Two studies revealed that microglial transplants placed into lesioned spinal cord promoted neurite growth (138;142). Although functional recovery was not documented in these latter reports, partial recovery was provided by transplanting activated monocytes into the caudal stump of transected rat spinal cord (143). The success of these pre-clinical models prompted a Phase I clinical trial.…”
Section: Immunomodulatory and Cell-specific Therapies For Scimentioning
confidence: 99%
“…Two studies revealed that microglial transplants placed into lesioned spinal cord promoted neurite growth (138;142). Although functional recovery was not documented in these latter reports, partial recovery was provided by transplanting activated monocytes into the caudal stump of transected rat spinal cord (143). The success of these pre-clinical models prompted a Phase I clinical trial.…”
Section: Immunomodulatory and Cell-specific Therapies For Scimentioning
confidence: 99%
“…42 Macrophages have also been shown to provide a suitable environment for central axonal regeneration. 43 The first experiments showing this effect involved the retina and many others have since followed. Fetal transplants have also been used in the brain of animals with variable results.…”
Section: The Autonomic Motor Systemmentioning
confidence: 99%
“…Clearly, the environment dictates the response of the macrophage. 68 Lymphocyte infiltration T-lymphocytes are scattered in the uninjured spinal cord and progressively increase in number after injury in parallel with the activation of microglia and influx of peripheral macrophages, within the first week and predominantly within the epicentre. 14 Under normal conditions, activated T cells can cross the BBB and enter the CNS parenchyma.…”
Section: Experimental Modelsmentioning
confidence: 99%